Marketing Communication Strategy Developing for Ban Yangilai and Ban Dongua Occupational Group, Ku Santarat Subdistrict, Mahasarakham District - Chaiala Sangrungruengroj, Phuangchompu (Journal of Applied Informatics and Technology, 2020)
This study proposed 1) to study marketing communication model of occupational groups 2) to develop a marketing communication strategy for the occupational group. The mixed research methods used included focus groups, interviews and surveys. The population of this study were splited into 2 groups; the community members of Yangilai and Dongua who were interested in establishing their own occupational group, and the consumer who have bought products from the occupational group. The researcher gathered data from 12 people from the community members 95 people from the consumers using accidental sampling. Statistics used in data analysis were percentage mean and standard deviation. The results showed that 1) the occupational group used social network as the main marketing communication channel to initiate conversations with their descendants, colleagues, or to wait formiddleman to buy for resale. The occupational group used social media in a lower level ( x̄ = 1.97). 2) the occupational group wanted to develop a new silk product called “silk breast cloth” used wrap over a shirt when women dress to join important ceremony especially merit making at temple which conforms to Nadoon district’s identity as being religiously civilized. Meanwhile, the customers rated “to support the community” as the top reason (29.5 percent) when buying products. A total amount of 301 – 400 baht was found to be the most frequent transaction (46.3 percent) spent by the customer group. The group received information on occupational products through the internet the most (44.2 percent). Recieved occupational Moreover, the data also showed that the marketing mixes that affect the customer decision were product-product usefulness (high level, x̄ = 4.24), price-suitable price (high level, x̄ = 4.37), channel of distribution-convenience (high level, x̄ = 3.78), promotion-advertising and public relations (high level, x̄ = 4.35). Therefore, the marketing communication guideline should portray the product value as being produced by community, gone through production process that inherited from the ancestors’ wisdom, and useful for belief and faith related purposes, including the beauty of the products in order forthe customers to perceive them as priceworthy. The elderly are deemed as potential message senders because they know by heart the needed information on production process and religiously civilized community. However, that the occupational group has a lower level of social media usage. Thus, it recommends that social media communication skills and knowledge to realize the use of social media for marketing communication should be emphasized. Keywords : Communication marketing; Social media; Occupational group